Don't turn out the lights eaudiobook A tribute to alvin schwartz's scary stories to tell in the dark. - Maberry, Jonathan (2020)
Featuring stories from R.L. Stine and Madeleine Roux, this middle grade horror anthology, curated by New York Times bestselling author and master of macabre Jonathan Maberry, is a chilling tribute to Alvin Schwartz's Scary Stories to Tell in the Dark. Flesh-hungry ogres? Brains full of spiders? Haunted houses you can't escape? This collection of 35 terrifying stories from the Horror Writers Association has it all, including ghastly illustrations from Iris Compiet that will absolutely chill readers to the bone. So turn off your lamps, click on your flashlights, and prepare—if you dare—to be utterly spooked! The complete list of writers : Linda D. Addison, Courtney Alameda, Jonathan Auxier, Gary A. Braunbeck, Z Brewer, Aric Cushing, John Dixon, Tananarive Due, Jamie Ford, Kami Garcia, Christopher Golden, Tonya Hurley, Catherine Jordan, Sherrilyn Kenyon, Alethea Kontis, N.R. Lambert, Laurent Linn, Amy Lukavics, Barry Lyga, D.J. MacHale, Josh Malerman, James A. Moore, Michael Northrop, Micol Ostow, Joanna Parypinksi, Brendan Reichs, Madeleine Roux, R.L. Stine, Margaret Stohl, Gaby Triana, Luis Alberto Urrea, Rosario Urrea, Kim Ventrella, Sheri White, T.J. Wooldridge, Brenna Yovanoff